2023
DOI: 10.1126/sciadv.abn5390
|View full text |Cite
|
Sign up to set email alerts
|

A dual organelle-targeting mechanosensitive probe

Abstract: Cells are responsive to the mechanical environment, but the methods to detect simultaneously how different organelles react in mechanobiological processes remain largely unexplored. We herein report a dual organelle-targeting fluorescent probe, ( E )-1-[3-(diethoxyphosphoryl)propyl]-4-[4-(diethylamino)styryl]pyridin-1-ium bromide (ASP-PE), for mechanical mapping in live cells. ASP-PE is aggregation-induced emission active and is sensitive to the local mechanical environment. It targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The resulting push–pull system causes a large red-shift of the absorption maximum and increases fluorescence lifetime, intensity, and quantum yield. This mode of action is contrary to other membrane probes that report off equilibrium in the excited state. In lipid bilayer membranes, these changes report on an increasing order from liquid-disordered (L d ) to liquid-ordered (L o ) and solid-ordered (S o ) membranes (Figure b). Tension applied to biomembranes increases fluorescence lifetimes because the probe response is dominated by membrane reorganization, particularly tension-induced phase separation (Figure c).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The resulting push–pull system causes a large red-shift of the absorption maximum and increases fluorescence lifetime, intensity, and quantum yield. This mode of action is contrary to other membrane probes that report off equilibrium in the excited state. In lipid bilayer membranes, these changes report on an increasing order from liquid-disordered (L d ) to liquid-ordered (L o ) and solid-ordered (S o ) membranes (Figure b). Tension applied to biomembranes increases fluorescence lifetimes because the probe response is dominated by membrane reorganization, particularly tension-induced phase separation (Figure c).…”
Section: Introductionmentioning
confidence: 75%
“…Fluorescent flippers have been introduced as small-molecule fluorescent probes to image membrane tension in living systems (Figure a–c) . For the imaging of biomembrane function, membrane tension is particularly interesting but also particularly demanding because physical forces are detectable only through the suprastructural changes they cause . Inspired by nature, we have considered the concept of planarizable push–pull probes to tackle this challenge .…”
Section: Introductionmentioning
confidence: 99%
“…The same group employed a semi-cyanine unit as the SO 2 -responsive site, a naphthalimide unit and semi-cyanine unit as the fluorophores, and semi-cyanine as well as morpholine groups to target mitochondria and lysosomes, constructing the first dual-targeting organelle-targeted fluorescent probe, DML-P ( 58 , Scheme 7 ), capable of tracing the mitochondria and lysosome SO 2 simultaneously [ 173 ]. Most recently, Ho et al utilized an electron push–pull π-conjugation skeleton and a rarely reported diethyl phosphonate moiety on the pyridinium ring to develop an AIE-based bioprobe, ASP-PE ( 59 , Scheme 7 ), for dual plasma membrane–mitochondria targeting through its phosphonate moiety and pyridinium, visualizing the changes in the membrane tension of the plasma membrane as well as mitochondria in response to varied osmotic pressure and substrate stiffness [ 174 ]. Therefore, this probe revealed the significance of actin and microtubules for plasma membranes and mitochondria in response to mechanobiological stimulations.…”
Section: Design Of Molecular Probes For Organelle-targeted Cell Imagingmentioning
confidence: 99%
“…[5] For their design, the bioinspired [51,52] concept of planarizable push-pull probes has been formulated, [5,51] which remains different from other smallmolecule approaches toward tension probes explored later on. [6][7][8]22,25,28,34,53] In brief, flipper probes are composed of two dithienothiophenes that are forced out of co-planarity by electrostatic repulsion from chalcogen-bond donors next to the twistable bond (Figure 1a, r). Mechanical planarization then brings the two dithienothiophenes into conjugation, which induces bathochromic shifts of absorption and excitation maxima and increases in fluorescence lifetime and quantum yield.…”
Section: Introductionmentioning
confidence: 99%
“…Small‐molecule fluorescent membrane probes are of central importance for bioimaging in living cells [1–5] . Depending on their design, the most common membrane probes respond to viscosity, [6–27] hydration, [1,3,26–40] thickness, [41–44] potential, [4,13–18,26,45–47] membrane order, [1–3,6,8,24,27–33] surface charge [39,40] and surface pH [12,36,48–50] by different mechanisms that mostly operate off equilibrium in the excited state. Fluorescent flippers have been introduced specifically as small‐molecule probes to image membrane tension and order in living systems by mechanical compression in equilibrium in the ground state (Figure 1a–d).…”
Section: Introductionmentioning
confidence: 99%